FIRST RECORD OF Leptobrachella shiwandashanensis CHEN, PENG, PAN, LIAO, LIU & HUANG, 2021 (ANURA: MEGOPHRYIDAE) FROM VIETNAM - Thi Ngam, Lo; Van Chung, Hoang; Quang Truong, Nguyen; Lan Hung Son, Nguyen; Ziegler, Thomas; The Cuong, Pham (Journal of Forestry Science and Technology, 2022)
Leptobrachella shiwandashanensis was originally described from the evergreen forest of Mount Shiwandashan, Guangxi province, China. We herein record this species for the first time from Vietnam based on a new amphibian collection from Quang Son commune, Hai Ha district, Quang Ninh province. Morphological characteristics of the specimens from Quang Ninh province, Vietnam resemble those of the type series from China in the following characteristics: small size; head wider than long; pale brown dorsal surfaces, with distinct dark brown inverse-triangle-shaped marking between eyes; flanks with irregular black spots; ventral surface creamy white with brown spots on lateral margin; throat and chest nearly immaculate creamy white; fingers and toes free of webbing; dermal fringes on sides of fingers and toes absent; tibio-tarsal articulation reaching to posterior of the eye; iris bicolored, upper half brownish-red, transitioning to silver in the lower half. However, the specimens from Vietnam slightly differ from the type series from China by having a smaller size in males and a somewhat different dorsal colour pattern in the female. Genetic divergences between sequences of the Vietnamese specimens and those of L. shiwandashanensis from China are approximate 1.7–1.9% (16S gene). In addition to our morphological and molecular comparisons, we provide first natural history notes of L. shiwandashanensis from Vietnam.